Impact of p53, HIF1a, Ki-67, CA-9, and GLUT1 Expression on Treatment Outcomes in Locally Advanced Cervical Cancer Patients Treated With Definitive Chemoradiation Therapy. (February 2021) - Gaber, Germaine; El Achy, Samar; Khedr, Gehan A.; Parimi, Vamsi; Helenowksi, Irene; Donnelly, Eric D.; Strauss, Jonathan B.; Woloschak, Gayle; Wei, Jian-Jun; Small, William; Refaat, Tamer
Abstract : Purpose/Objective: The objective of this study was to assess the association between pretreatment p53, hypoxia inducible factor 1a (HIF1a), Ki-67, carbonic anhydrase-9 (CA-9), and glucose transporter 1 (GLUT1) expression in locally advanced cervical cancer patients treated definitively with concurrent chemoradiation therapy (CRT) and treatment outcomes including overall survival (OS), progression-free survival (PFS), local-regional control (LC), and distant metastases–free survival (DMFS). Patients and Methods: Twenty-eight patients treated definitively and consecutively for cervical cancer with CRT had p53, HIF1a, Ki-67, CA-9, and GLUT1 protein expression assessed and scored semiquantitatively by 3 pathologists, blinded to the treatment outcomes. Outcomes were stratified by p53 ( H -score: <15 vs. ≥15), HIF1a ( H -score: <95 vs. ≥95), Ki-67 (labeling index <41% vs. ≥41%), CA-9 ( H -score: <15 vs. ≥15), and GLUT1 ( H -score: <175 vs. ≥175) expression. OS, PFS, LC, and DMFS rates were calculated using the Kaplan-Meier method, and differences between groups were evaluated by the log-rank test. Results: Notable clinical characteristics of the cohort included median age of 51 years (range: 32 to 74 y), FIGO stage IIB disease (57.2%), clinical node-negative disease (64.3%), squamous cell carcinoma (89.3%), and adenocarcinoma (10.7%). Treatment outcomes included 5-year OS (57.2%), PFS (48.1%), LC (72.1%), and DMFS (62.9%). For HIF1a H -score <95 and ≥95, the 5-year OS (52.0% and 68.4%, P =0.58), PFS (53.0% and 40.9%, P =0.75), LC (71.6% and 68.2%, P =0.92), and DMFS (59.7% and 52.0%, P =0.91) were not significantly different. For Ki-67 labeling index <41% and ≥41%, the 5-year OS (44.9% and 66.6%, P =0.35), PFS (38.9% and 55.4%, P =0.53), LC (57.7% and 85.7%, P =0.22), and DMFS (67.3% and 61.0%, P =0.94) were not significantly different. For CA-9 H -score <15 and ≥15, the 5-year OS (54.4% and 66.7%, P =0.39), PFS (57.3% and 40.0%, P =0.87), LC (70.0% and 70.0%, P =0.95), and DMFS (70.0% and 46.7%, P =0.94) were not significantly different. For GLUT1 H -score <175 and ≥175, the 5-year OS (43.6% and 43.6%, P =0.32), PFS (55.6% and 49.5%, P =0.72), LC (72.9% and 71.5%, P =0.97), and DMFS (62.5% and 59.6%, P =0.76) were not significantly different. For p53, H -score <15 and ≥15, the 5-year OS (62% and 53%), PFS (63% and 30.3%), LC (87.5% and 52%), and DMFS (79.6% and 41.6%). Conclusions: In this study population, HIF1a, Ki-67, CA-9, and GLUT1 expression did not predict treatment response or outcomes in locally advanced cervical cancer patients treated definitively with CRT. There was a nonstatistically significant trend towards worse outcomes with p53 expression.